(untitled) (Fiep Bulletin - online, 2016)
This study examined the knowledge of the physical education teachers about first aid procedures applicable to students of municipal primary schools in Ponta Grossa. With the participation of 21 teachers from 19 schools, with 52.4% female and 47.6% male. The proposed methodology was a questionnaire containing 11 questions about procedures to be applied to students in case of accidents, as well as issues related to first aid kits in schools. The data analysis and formulating graphs positive values ??(0.25 were performed using Excel 2007. By assigning values ??varying from 0 (zero) for the answers considered correct within the standards of care provided, and - 0, 5 to 0.75 and 1) to those considered non-standard in emergency care. Through this work we verified the importance of discipline in the first aid course grade physical education, and the need for ongoing training for teachers to work accurately and effectively in the event of accidents during class.